ROLE OF HONEY IN WOUND DRESSING IN DIABETIC FOOT ULCER - Surahio, Abdul Rashid; Khan, Ashar Ahmad; Farooq, Main Usman; Fatima, Iffat (Journal of Ayub Medical College Abbottabad, 2014)
Background: Honey has antibacterial and antimicrobial properties. This study was conducted to evaluate the efficacy and role of honey as local wound dressing agent in the management of diabetic foot and its effect on rate of amputation. Method: This prospective observational study was done in the general surgery department, Al- Noor Specialist hospital, Holly Makkah, KSA from 1st March, 2007 to 31st May, 2008 (15 months). This study includes 172 patients of either gender, above 18 years of age, belonging to different nationalities admitted to Al- Noor specialist hospital, Holly Makkah, KSA. Results: A total of 172 patients with male to female ratio 1.54:1 were admitted from 1st March, 2007 to 31st May, 2008 with complicated and non-healing diabetic foot ulcers. Out of these 172 patients, 135 (78.48%) were Saudi and 37 (21.52%) were non Saudi residents with ratio of 3.6:1. After admission and resuscitation, all the patients under went early surgical debridement and dressing with the thick layer of honey locally available. Wounds became healthy within 7-35 days. Three patients (1.75%) underwent big toe amputation and 2 (1.16%) patients under went below knee amputations. Twenty (11.6%) patients under went split skin grafting to cover the wound while in other patients wound healed by secondary intention. Conclusion: Use of honey significantly reduced rate of amputation and improve wound healing when used for wound dressing in chronic diabetic foot ulcers. Keywords: Diabetic foot ulcer, honey, dressing